Furniture design : Coffee table using recycle materials (solid wood waste) / Ahmad Shukry Md Razali - Md Razali, Ahmad Shukry (Faculty of Applied Sciences, 2016)
Nowadays, the demand for raw material (solid wood) is increasing for furniture industries. Due to the increasing on the raw material demand, another resource need to replace the material used now. One of the possible solution is by producing furniture using recycle wood waste. The objective of this study to design a coffee table using recycle material (recycle furniture and recycle solid wood) and still fulfill customer requirement. Survey is done to evaluate the customer satisfaction on the product. The questionnaire was given to 100 correspondents with different ages, gender, and profession. The questionnaires consist of the finishing process, aesthetic value, product price, type of raw material used in making the product and the design of the product. The data has been analyzed and discussed. From this study, it can be concluded that the coffee table can be accepted by all age level, gender and also profession. The majority of the correspondent realizes that the coffee table can attract people by its own design and the type of material used to make the product can give good advantage for furniture industry.